FIELDS EXCITED AND PROVIDING A UNIFORM FOCUSING OF SHORT RELATIVISTIC ELECTRON BUNCHES IN PLASMA - Maslov, Vasyl I.; Onishchenko, Ivan N.; Yarovaya, I. P. (East European Journal of Physics, 2014)
Plasma wake lens in which all short relativistic electron bunches of sequence are focused identically and uniformly is studied analytically and by numerical simulation. For two types of lenses necessary for these parameters of focused sequence of relativistic electron bunches are formulated. Verification of these parameters is performed by numerical simulation.